Project Management Competences by Teaching and Research Staff for the Sustained Success of Engineering Education - Alberto Cerezo-Narváez; Ignacio de los Ríos Carmenado; Andrés Pastor-Fernández; José Luis Yagüe Blanco; Manuel Otero-Mateo (Education Sciences, 2019)
Projects have become an essential instrument for the success of universities. In a context of globalization and increasing complexity, they must sharpen their resourcefulness to face these challenges and adapt to this changing environment. To reach these objectives, they undertake a series of activities of a unique, concrete and temporary nature, not always technical but managerial ones. If universities work with people on projects in the production, transmission and dissemination of knowledge, then they link with society to solve its problems. For this reason, teaching and research staff (TRS) should promote a range of professional project management (PM) competences in different areas for the proper management of the projects in which they take part. Through a Delphi technique, a panel of twenty-four accredited teaching experts who are carrying out significant research and holding directive roles, measured the importance of acquiring and/or improving professional PM competences by their TRS. Consensus and stability reached after two rounds of consultation confirmed there are a series of crucial competences for the practice of relevant teaching and pioneer research. Results obtained are the basis for a gap plan that allows the TRS to participate in and/or lead university projects with greater self-confidence and personal motivation.